Theories of knowledge sharing behavior in business strategy - Abdul Razak, Norfadzilah; Pangil, Faizuniah; Mohd Zin, Md. Lazim; Mohamed Yunus, Noor Azlina; Asnawi, Nini Hartini (Elsevier Ltd., 2016)
Inspiring people to share knowledge and experience at workplaces has gained attention among the researchers to determine the ways of motivating employees to knowledge sharing behavior. In order to promote knowledge-sharing behavior, people in business need to understand the influences and the mechanism that drives individually to contribute their valuable knowledge with others. This paper reviews the nature of knowledge sharing and theories underlying knowledge sharing behavior to understand the factors that influence individual behavior to share their knowledge. Several theories have been applied to study knowledge-sharing behavior included theory of reasoned action (TRA), theory of planned behavior (TPB) and social exchange theory (SET). The literature review was conducted to identify the association of the theories, practices and knowledge sharing behavior. Initial discussion in this paper, was discussing the nature of knowledge sharing and common practices of knowledge sharing behavior. The literature review determined willingness, business citizenship behavior and commitment represent as an individual knowledge sharing behavior. While, the theories identified that attitude, subjective norms, perceived behavioral control, and exchange of maximizing benefits and minimize cost in turn leads to drive individual towards knowledge sharing behavior. The finding contributes to the individual and business in understanding the factors that drive to knowledge sharing behavior.